Analisis Peran Gender Terhadap Perbedaan Minat Dan Partisipasi Anak Dalam Pembelajaran STEAM - Tumbularani Tumbularani; Raden Rachmy Diana (UIN Sultan Maulana Hasanudin Banten, 2024)
Gender stereotypes that are unconsciously instilled in children's family and social environment can influence their views on learning methods. This study aims to see how gender plays a role in differences in children's interest and participation in STEAM Learning. The population of this study is early childhood in RA Al-Hikmah Beringin District, Deli Serdang Regency, North Sumatra with a sample of 5-6 years old children totaling 20 children. The results obtained are that there are differences between the interest and participation of boys and girls in STEAM learning. Overall, girls are superior with a percentage of interest and participation of 75.56% and 76.25% while boys are 73.60% and 75.50%. Factors that influence this can be caused by internal factors, namely the characteristics of different ways of thinking between men and women. The external factors that have a strong influence on children's interest and participation in STEAM learning are differences in culture, religion, customs, society, value systems, and certain ethnic groups.